Strategies for Navigating Common Ethical Dilemmas Encountered by Operational Radiation Safety Professionals - Emery, RJ (Health Phys, 2016)
Because operational radiation safety professionals can encounter ethical dilemmas in the course of their work, codes of ethics and professional standards of conduct are maintained by the Health Physics Society (HPS) and the American Academy of Health Physics (AAHP). While these works provide valuable guidance, they do not operationalize the types of ethical dilemmas radiation safety practitioners might encounter. For example, consider the ethical conundrum of “dual loyalty”, defined as the situation in which an individual holds simultaneous obligations to two or more parties. In the case of radiation safety, practicing professionals hold obligations to the workers being protected and to the leaders of the organization. If these obligations are in conflict, serious difficulties can arise. The conundrum of dual loyalty is described and a strategy for reducing its effect is discussed. Two other common ethical issues; “confidentiality” and “organizational dissent” are similarly presented. A foundation from which to launch an ongoing dialogue about ethical issues within the radiation safety profession is also proposed.